2018
DOI: 10.1016/j.pcad.2018.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and the Obesity Paradox in Heart Failure

Abstract: Obesity continues to be a public health problem in the general population, and also significantly increases the risk for the development of new-onset heart failure (HF). However, in patients with already-established, chronic HF, overweight and mild to moderate obesity is associated with substantially improved survival compared to normal weight patients; this has been termed the "obesity paradox". The majority of studies measure obesity by body mass index, but studies utilizing less-frequently used measures of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
189
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 278 publications
(205 citation statements)
references
References 69 publications
10
189
0
6
Order By: Relevance
“…Along these lines, in CHD, it appears that there is a solid obese paradox, especially with BMI, yet additionally with BF and central obesity, displaying the best forecast noted in overweight CHD individual rather than those with more extreme weight . Thus, an investigation by Clark et al demonstrated that both higher BMI and higher WC were related to better HF occasion–free survival …”
Section: Textmentioning
confidence: 98%
“…Along these lines, in CHD, it appears that there is a solid obese paradox, especially with BMI, yet additionally with BF and central obesity, displaying the best forecast noted in overweight CHD individual rather than those with more extreme weight . Thus, an investigation by Clark et al demonstrated that both higher BMI and higher WC were related to better HF occasion–free survival …”
Section: Textmentioning
confidence: 98%
“…Furthermore, greater lean mass, which can be reflected in a higher BMI, is associated with better cardiorespiratory fitness levels. Greater fitness levels may be associated with an improved health condition [72,73].…”
Section: Obesity Paradoxmentioning
confidence: 99%
“…This has been studied in various cardiovascular and cerebrovascular disorders. [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] Observation of obesity paradox in intracerebral hemorrhage is reported in fewer studies. Of interest for our study, Dangayach et al 37 reported an overweight or obese status (BMI 25 kg/m2) was associated with twice the odds of having a good outcome compared with patients with BMI less than 25 kg/m2.…”
Section: Discussionmentioning
confidence: 99%